Evaluation of Pediatric Patient Admissions and Outcomes in Adult Intensive Care Units Over a 5-Year Period - Azime Bulut; Fatma Alkan Bayburt; İlke Tamdoğan; Muhammet Bulut (Çocuk Dergisi)
Objective: This study aimed to outline the demographic characteristics and mortality rates of pediatric patients managed in the adult intensive care units (ICUs) of Giresun Training and Research Hospital from 2018 to 2023.Methods: We conducted a retrospective review of records pertaining to 74 patients aged between 6 months and 18 years who were admitted to our ICU and received treatment for 24 h or more. Data collected included patient age, gender, diagnosis, APACHE II scores, requirement for mechanical ventilation, length of stay, Glasgow Coma Scale scores, and mortality rates.Results: Among the patients included, 59.4% were male, with an average age of 7.79±5.7 years. Most admissions were due to trauma (n = 57, 77.02%). The mean ICU stay was 3.78±3.37 days, and out of the 70 patients who completed their follow-up at our hospital, 4 (5.71%) died.Conclusions: Similar to global trends, a significant proportion of pediatric intensive care cases in our country are managed in adult ICUs. Mortality and morbidity vary based on the severity of the patient’s condition. Consideration should be given to implementing training programs for adult ICU teams until the availability of pediatric ICU beds and specialists is adequate.